Refined power follower strategy for enhancing the performance of hybrid energy storage systems in electric vehicles - Mohammad Al Takrouri; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz; Razman Ayop; Wen Yao Low (Results in Engineering)
Hybrid energy storage systems (HESS), combining lithium-ion batteries and supercapacitors (SC), are increasingly used in electric vehicles (EVs) to leverage the high energy density of batteries with the high-power density of SC. Effective operation of HESS relies on an energy management strategy (EMS) that efficiently balances power distribution. The standard power follower (PF) EMS is widely used but can induce abrupt battery current changes, impacting battery health. This study introduces a refined PF EMS employing an exponential smoothing function with a single adjustable parameter to stabilize SC reference power, reducing abrupt transitions in battery current. A comprehensive evaluation was conducted through both large-scale simulations and small-scale experimental setups. Simulations, using a tuned smoothing factor of α = 0.03, demonstrated that the refined EMS achieved balanced performance across various sdriving cycles, with RMS battery current reductions of approximately 4.5 % in the new European driving cycle (NEDC) and 2.2 % in the worldwide harmonized light vehicles test cycle (WLTC). Experimental validation on a small-scale setup verified these improvements, demonstrating a reduction in peak battery current to 0.674 A, which outperforms the original PF (0.754 A) and FS (1.297 A) methods. Additionally, the proposed EMS achieved an 18.73 % reduction in RMS battery current compared to the original PF while maintaining a balanced rate of change (ROC) at 208.21 A/s. These findings emphasize the refined EMS's potential to enhance battery lifespan and energy efficiency, offering a practical and scalable solution for EV applications.